Using Molecular Diagnostics to Develop Therapeutic Strategies for Carbapenem-Resistant Gram-Negative Infections - Tenover, Fred C. (Frontiers in Cellular and Infection Microbiology, 2021)
Infections caused by multidrug-resistant Gram-negative organisms have become a global threat. Such infections can be very difficult to treat, especially when they are caused by carbapenemase-producing organisms (CPO). Since infections caused by CPO tend to have worse outcomes than non-CPO infections, it is important to identify the type of carbapenemase present in the isolate or at least the Ambler Class (i.e., A, B, or D), to optimize therapy. Many of the newer beta-lactam/beta-lactamase inhibitor combinations are not active against organisms carrying Class B metallo-enzymes, so differentiating organisms with Class A or D carbapenemases from those with Class B enzymes rapidly is critical. Using molecular tests to detect and differentiate carbapenem-resistance genes (CRG) in bacterial isolates provides fast and actionable results, but utilization of these tests globally appears to be low. Detecting CRG directly in positive blood culture bottles or in syndromic panels coupled with bacterial identification are helpful when results are positive, however, even negative results can provide guidance for anti-infective therapy for key organism-drug combinations when linked to local epidemiology. This perspective will focus on the reluctance of laboratories to use molecular tests as aids to developing therapeutic strategies for infections caused by carbapenem-resistant organisms and how to overcome that reluctance.